Usability Testing of MOOC Prototype Using SUS (System Usability Scale) Method - Hidayat, Asep Syaiful; Santosa, Paulus Insap; Hidayah, Indriana (2022)
One way to improve civil servants' performance is competency development. Training is part of competency development that is widely used but still has limitations in implementation. There is a new idea with the use of e-learning in training that is expected to solve the various shortcomings of the classical training model. MOOC (Massive Open Online Course) is a currently popular e-learning model with an open and unlimited character expected to be applied in training with constraints on space and time limitations. This research discusses the usability test on the MOOC prototype that has been made using Axure software. Usability testing of the prototype uses the System Usability Scale (SUS) method to measure the usability level of a system on the user side. The result of the SUS score is 72.75, which means it has a suitable category for the system to be used as a reference to continue the implementation of application development. © 2022 IEEE.